A beginner's guide to creating iPhone apps for iOS 15 using Swift UI (Packt Publishing, 2022)
Learn to create apps and submit them to the App Store using SwiftUI 3 Code and Xcode 13 on iOS 15 from scratch About This Video Develop iPhone apps using SwiftUI 3 code and Xcode 13 Learn Swift programming and SwiftUI by creating five complete apps Learn to share your app ideas through the App Store In Detail If you are looking for a course that is fun, for complete beginners, and gets straight to the point, then this is the course for you. This course will help you learn all about developing iPhone applications and simultaneously implement all that you learn by creating five complete apps using SwiftUI 3 code and Xcode 13. In this course, we will start with the SwiftUI basics that are required for developing an app and set up our developing environment with Xcode. Once our environment is set, we will start working on our different apps. In this first app - People Counter - and the second app - Text Formatter, you will be learning the basics of Swift programming. In this third app, we will create an app called Emoji Dictionary, where you will learn about lists, arrays, and multi-view apps. In the fourth app, we will create a Quick ToDos app, where you will learn how to save information with CoreData. In our final app, we will create a Course Lister app where we will work with web, APIs, JSON, and images. Once we are done with the apps, we will discuss the process to submit your own apps to the App Store! By the end of this course, you will be set to build your own app and share your app with the world through the App Store. Who this book is for This course is best for complete beginners who want to make an iPhone app as no prior experience is needed and one just needs to have a Mac computer and passion to develop amazing apps.